Growth Concerns in Coffin-Lowry Syndrome: A Case Report and Literature Review - Ying Lv; Liuyan Zhu; Jing Zheng; Dingwen Wu; Jie Shao (Frontiers Media S.A., 2019)
Mutation of RPS6KA3 can induce Coffin-Lowry syndrome, an X-linked syndrome. The case here reported manifests its signature characteristic of short stature, facial dysmorphism, development retardation, hearing defect. The mutation of RPS6KA3 we detected by NGS analysis is c.2185 C > T. The short stature is a noteworthy problem we discuss here to improve the patient's growth and development. The efficacy and safety of application of growth hormone analogs on patients with CLS are not confirmed and need to be carefully considered.